A Study of Relationship between Thinking Style, Attitude towards ICT and Computer Confidence among Student Teachers - Bijoy K. Thomas (Researchparks Publishing, 2023)
Thinking, a very convoluted process is the mental phenomenon that is most difficult to elucidate or express in terms of complexity. Each individual's unique way of taking in and processing the information they encounter is their